'Its Object is Not to Degrade, But to Elevate': Reflecting on Preventive Detention in the Early 20th Century. (11th October 2021) - BENNETT, RACHEL
Abstract: In response to growing concerns about habitual criminality and its impact upon the fabric of society, the Prevention of Crime Act 1908 stipulated that when the courts passed a sentence of penal servitude upon repeat offenders, they could additionally pass a sentence of preventive detention if it was deemed expedient for the protection of the public. Reflecting upon the commentaries of those who worked within the preventive detention institution at Camp Hill, this article explores the rationale underpinning the regime and examines the management of the historic question facing the prison system, namely how prisoners should be 'doing time' and how prisons should be using this 'time'.